Man stuff : thoughts on faith, family, and fatherhood - Turner, Josh; Robertson, Jase, 1969- (Nashville : Countryman, a division of Thomas Nelson Publishers, 2014)
"In this compilation, Josh shares fun and meaningful thoughts and personal stories--ranging from his childhood years to today--and weaves in spiritual insight for men who want to be better dads, husbands, and men of God. He covers a variety of topics such as living and working with integrity, facing your fears, surrounding yourself with good company, trusting God's plans, standing up for the least of these--topics every man can relate to and draw from to grow in his spiritual and personal journeys."--Publisher's description.
Foreword by Jase Robertson of A&E's Duck dynasty.
Keywords: Turner, Josh; Fathers -- Biography; Christian life; Country musicians -- Biography